Determination of Depleted Uranium Concentration and Histopathological Changes in Local Iraqi Fish and Chickens - Neamah, Ghusoon Abdul Kareem; Yousif, Eman Hashim (The Iraqi Journal of Veterinary Medicine, 2019)
This study aimed to determine the concentration of depleted uranium and the main histopathological changes in local fish and chickens at a selected Iraqi area suspected to be polluted with uranium. Different locations of Al-Tuwaitha region (Southern of Baghdad) were surveyed randomly to collect a total of 15 samples from each animal species. The animals were sacrificed and dissected at the site of collection. Muscle samples were collected to determine uranium concentrations using nuclear fission track analysis with CR-39 detectors. For histopathological changes, sample tissues from fish (liver, gills, and kidney) and chickens (liver, kidney, and lung) were collected and fixed in 10% neutral buffered formalin. The results showed that there was a significant elevation in uranium concentration in both fish and chicken muscles (1.94±0.77 µg/Kg and 2.19±0.82 µg/Kg, respectively) compared with recommended uranium concentration. Histopathological examination showed several effects included congestion and thickening of blood vessels walls, vacuolation, necrosis, fibrosis and inflammatory cells infiltration in most tissue section of collected organs. In conclusion, the uranium residues that found in both fish and chicken meats could raise the concerns about consumption of both animal species that had been bred in Al-Tuwaitha, and could be an indicator of environmental pollution with uranium in this region.